THE IMPORTANCE OF TAXONOMIC CLASSIFICATION OF ‘PASHACO’ AND ‘HUAYRURO’ IN THE FABACEAE FAMILY FOR TIMBER PRODUCTION IN LORETO, PERU - Villacorta Gonzales, Carlos; Del Aguila Mendoza, Lizbeth Carolina; Rios Paredes, Marcos Antonio; Bartolo Cuba, John Albert; Silva Moreno, Henri Frank; Welling, Johannes (Floresta, 2024)
In Peru, forest inventories traditionally group different timber species under the same commercial name. The names "pashaco" and "huayruro" in the Amazon exemplify this practice, representing the grouping and commercialization of various Fabaceae species, a family of significant forest and commercial importance in Loreto. This study aimed to taxonomically identify the "pashaco" and "huayruro" individuals a timber company recorded in its forest census and to differentiate each group's species through dendrological characterization. The company's census identified 429 "pashaco" individuals as Albizia niopioides and 150 "huayruro" individuals as Ormosia amazonica. Botanical identification of samples from 80 individuals in each group revealed that the individuals classified as A. niopioides comprised nine species: Schizolobium parahyba var. amazonicum, Dimorphandra cuprea, Pseudopiptadenia suaveolens, Hydrochorea pedicellaris, Enterolobium schomburgkii, Parkia nitida, Parkia igneiflora, Parkia decussata, and Parkia multijuga, with the last being the most common. Similarly, the "huayruro" or Ormosia amazonicaclassification included Andira macrothyrsa, Batesia floribunda, Ormosia coccinea, Ormosia amazonica, Vataireopsis surinamensis, Vatairea erythrocarpa, Hymenolobium excelsum, Hymenolobium nitidum, and Hymenolobium velutinum, with the latter being the most abundant. This study underscores the need for improved species identification in forest inventories. Dendrological characteristics of stems and leaves can aid in differentiating and identifying these species in forest censuses, fostering sustainable management practices by reducing species grouping and minimizing economic impacts in the timber forest production chain.